Efficacy of coronary fractional flow reserve using contrast medium compared to adenosine - Topcu, Selim; Tanboğa, Ibrahim Halil; Aksakal, Enbiya; Aksu, Uğur; Gulcu, Oktay; Birdal, Oğuzhan; Arısoy, Arif; Kalaycı, Arzu; Ulusoy, Fatih Rifat; Sevimli, Serdar (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2016)
Aim: To compare the contrast medium induced Pd/Pa ratio (CMR) with the FFR. Material and methods: We enrolled 28 consecutive patients with 34 intermediate lesions who underwent coronary FFR measurement by intracoronary (i.c.) adenosine. After baseline Pd/Pa was calculated, a single contrast medium (Iomeron) injection of 6 ml (3 ml/s) was performed manually. Within 10 s after the contrast medium injection, the CMR was calculated. Bolus injection of i.c. adenosine was performed to induce maximal hyperemia (from 60 µg to 600 µg), and when it was ≤ 0.80, the intermediate lesion was considered as significant. Results : After bolus i.c. adenosine, 12 lesions of 34 (35.3%) were identified as significant. The CMR value was 0.86 ±0.06 (range: 0.71–0.97). There were no significant differences between FFR and CMR values (p = 0.108). A substantial positive correlation between adenosine and contrast values was detected (0.886 and p < 0.001). Good agreement in Bland-Altman analysis was revealed (mean bias was 0.027, 95% confidence interval 0.038–0.092). Receiver operating characteristics curve analysis showed 90.9% sensitivity and 91.7% specificity for a cut-off value of 0.85 for the CMR compared to FFR (≤ 0.80). Conclusions : Our study showed that measuring the CMR is a feasible method compared to FFR. The CMR may be used in situations where adenosine cannot be administered.